HISTORICAL REVIEW OF THE INSTITUTE OF APPEAL AND ITS DEVELOPMENT CHARACTERISTICS - Nino Tsikhiseli (European Scientific Journal, ESJ, 2015)
The presented work - “Historical Review of the Institute of Appeal and Its Development Characteristics” concerns the Appeal and its legal nature. The work is about the historical development and the establishment of appeal in various countries. In the work the following issues are defined: essence of Appeal, notion of Appeal and complete (unlimited) and incomplete (limited) types of Appeal.